Handbook of research on Catholic higher education - Hunt, Thomas C., 1930-; Nuzzi, Ronald J.; Joseph, Ellis A.; Geiger, John O. (Emerald Publishing Limited : Information Age Pub., 2003)
The Handbook of Research of Catholic Higher Education provides an important and timely overview for scholars and students interested in understanding this important sector of private higher education. More importantly, it is an important resource for those faculty, staff, and administrators interested in shaping the distinctiveness of Catholic colleges and universities. The Handbook provides chapters presenting a thematic overview of a particular element of Catholic higher education and in addition provides an extensive bibliography resource of further reading. While some of the chapters will appeal to those with specialized interests, e.g. legal affairs, finance, and community relations, the chapters on mission and religious identity, history, and the documents on Catholic higher education provide an important perspective on the challenges facing Catholic higher education and should be read by everyone involved in Catholic colleges and universities. The Handbook of Research of Catholic Higher Education is an important resource for understanding and shaping the distinctiveness of Catholic higher education.